Preparing Future Teachers for the Development of Students’ Emotional Intelligence - Dubovyk, Svitlana H.; Mytnyk, Alexander Ya.; Mykhalchuk, Nataliia O.; Ivashkevych, Ernest E.; Hupavtseva, Nataliia O. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: This study deals with the issues of preparing future educators for the development of students’ emotional intelligence. The study aims to identify the most important aspects of future teachers training in the framework of this task, to identify the main factors that should be paid attention to when training teachers, whose tasks in the future will include the development of emotional intelligence of school students. Background: Particular attention is paid to the study of the training of teaching staff for the development of emotional intelligence in students with psychological disturbances. The object of the study is the branches of pedagogy of higher education aimed at educating qualified teaching staff that can effectively solve the tasks of developing the emotional intelligence of elementary school students. Method: In the study, methods of system analysis of the subject matter are used, based on a detailed examination of the studies of the material available for research, with a qualitative analysis of all the collected information. Results: Based on the conducted studies were formed recommendations on the training of teachers for future practical activities within the framework of the issues under consideration, which are summarised as follows: in training, attention should be paid to working with educational games, the task of which is to develop students’ skills in identifying and evaluating emotions, their own and of students participating in the game, the study and analysis of works of classical literature, as a method of learning to think, analyse and develop the emotional sphere, training in the implementation of special exercises for the development of the emotional sphere. Conclusion: The study has important applied value in terms of expanding the understanding of emotional intelligence and the need for its development, starting from the lower grades of high school.